The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1108/13555850110764757
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐cultural examination of the general theory of marketing ethics: does it apply to the next generation of managers?

Abstract: This research confirms the empirical test of Hunt and Vitell's (1986) General Theory of Marketing Ethics by Mayo and Marks (1990) across four cultures. Using path analysis, the core relationships of the general theory of marketing ethics, as originally tested by Mayo and Marks (1990) were successfully replicated using over 1500 students from seven universities in the US, Canada, Netherlands, and Australia. "Tomorrow's managers" appear to use a more deontological approach to making ethical judgments about perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…[and] the relationship between judgments and intentions to adopt an ethical alternative is attenuated when its implementation does not result in a preferred consequence" (p. 163). Donoho et al (1999) replicated Mayo and Marks's (1990) research across four different national populations, finding evidence consistent with Mayo and Marks's original results.…”
Section: Empirical Tests Of the Theorysupporting
confidence: 73%
“…[and] the relationship between judgments and intentions to adopt an ethical alternative is attenuated when its implementation does not result in a preferred consequence" (p. 163). Donoho et al (1999) replicated Mayo and Marks's (1990) research across four different national populations, finding evidence consistent with Mayo and Marks's original results.…”
Section: Empirical Tests Of the Theorysupporting
confidence: 73%
“…Hunt and Vasquez-Parraga (1993) study found gender as a personal characteristic that shapes managers' ethical decisions. Burns and Kiecker (1995), Donoho et al (1999), Mayo and Marks (1990), Menguc (1998), andVitell et al (2001) studied the impact of deontological versus teleological orientations of the decision maker. Bommer et al (1987) proposed a normative ethical decision model and argued that individual attributes of the decision maker, the work environment, professional environment, personal environment, social environment, and government/legal environment affect ethical/unethical behavior.…”
Section: Factors Affecting Ethical Behaviormentioning
confidence: 99%
“…Ethical issues in social media embraces identity, privacy, surveillance, friending, and user exploitation (Donoho et al, 2001) on the other hand consumer behaviour have also attracted considerable attention in the last few decades (Al-Khatib et al, 1997;Singhapakdi et al, 1999;Wood, 2017). However, there are limited empirical studies focusing on ethical issues associated with social media engagement and their effects on consumer preferences.…”
Section: Introductionmentioning
confidence: 99%